EXAMINING EXAMINING HOW FAMILY ENVIRONMENT AND LEARNING INDEPENDENCE AFFECT STUDENT LEARNING MOTIVATION AT MI BABUSSALAM KRIAN SIDOARJO - irawan, alfiatul izzati; Didit Darmawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
In learning activities, motivation can be interpreted as the force that drives student learning activities. This motivation becomes a driving factor within students that drives the learning process which ensures the continuity of learning activities and provides the direction needed so that the goals desired by students can be achieved. For this reason, this research focuses on the influence of the family environment and learning independence on students' learning motivation at MI Babussalam, Krian, Sidoarjo. With a total population of 650 students at MI Babussalam, this research used a sample of 90 students from class 6. Sampling was carried out randomly to ensure sample representativeness of the larger population. By using a quantitative research design, this research aims to measure and analyze the influence of these variables on student learning motivation. This research resulted in the finding that the family environment and learning independence significantly influence the learning motivation of students at MI Babussalam, Krian, Sidoarjo. A conducive family environment and the level of student learning independence can increase student learning motivation at MI Babussalam. These results provide a better understanding of the factors that need to be considered in increasing student learning motivation at the MI level. Keywords: Learning Motivation; Family Environment; Learning Independence.